Association of weather, air pollutants, and seasonal influenza with chronic obstructive pulmonary disease hospitalization risks. (15th January 2022) - Chong, Ka Chun; Chen, Yu; Chan, Emily Ying Yang; Lau, Steven Yuk Fai; Lam, Holly Ching Yu; Wang, Pin; Goggins, William Bernard; Ran, Jinjun; Zhao, Shi; Mohammad, Kirran N.; Wei, Yuchen
Abstract: The influences of weather and air pollutants on chronic obstructive pulmonary disease (COPD) have been well-studied. However, the heterogeneous effects of different influenza viral infections, air pollution and weather on COPD admissions and re-admissions have not been thoroughly examined. In this study, we aimed to elucidate the relationships between meteorological variables, air pollutants, seasonal influenza, and hospital admissions and re-admissions due to COPD in Hong Kong, a non-industrial influenza epicenter. A total number of 507703 hospital admissions (i.e., index admissions) and 301728 re-admission episodes (i.e., episodes within 30 days after the previous discharge) for COPD over 14 years (1998–2011) were obtained from all public hospitals. The aggregated weekly numbers were matched with meteorological records and outdoor air pollutant concentrations. Type-specific and all-type influenza-like illness positive (ILI+) rates were used as proxies for influenza activity. Generalized additive models were used in conjunction with distributed-lag non-linear models to estimate the associations of interest. According to the results, high concentrations of fine particulate matter, oxidant gases, and cold weather were strong independent risk factors of COPD outcomes. The cumulative adjusted relative risks exhibited a monotone increasing trend except for ILI+ B, and the numbers were statistically significant over the entire observed range of ILI+ total and ILI+ A/H3N2 when the reference rate was zero. COPD hospitalization risk from influenza infection was higher in the elderly than that in the general population. In conclusion, our results suggest that health administrators should impose clean air policies, such as strengthening emissions control on petrol vehicles, to reduce pollution from oxidant gases and particulates. An extension of the influenza vaccination program for patients with COPD may need to be encouraged: for example, vaccination may be included in hospital discharge planning, particularly before the winter epidemic. Graphical abstract: Image 1 Highlights: PM2.5 is an independent risk factor of chronic obstructive pulmonary disease (COPD). Cold weather is a risk factor of COPD admission and re-admission. Oxidant gases was associated with COPD re-admission. Seasonal influenza, particularly type A/H3N2 is related with both COPD outcomes. COPD risk from influenza is higher in the elderly than that in general population.